RELIGIUSITAS, SPIRITUALITAS DAN POTRET PENDIDIKAN DI KOMUNITAS MUSLIM BADUY - Dadan Sunandar; Naf’an Tarihoran (Journal of Innovation Research and Knowledge, 2022)
The portrait of education in the Baduy community is very unique and interesting, the local wisdom of the Baduy community, which until now still exists and continues to be maintained, contains many cultural values. Culture and education have a very close relationship that cannot be separated. The purpose of this study will be to discuss about Religiosity, Spirituality and Portraits of Education in the Baduy Muslim Community. This research is a qualitative descriptive study with descriptive analysis which will describe the situation in the research field not with numbers but with descriptive words. The results of the study reveal that the education model applied to the Baduy community is a community-based education model where education is based on religious, cultural, social characteristics, aspirations and community potential as a manifestation of education from and for the community. So that the implementation of education involves traditional leaders, community leaders and religious leaders. The reason is because the community is an educational resource that has the potential to realize the education that is aspired so that the existing religiosity is increasing and spiritualism has the ability to build education and religious angles well.